Nutrition Counseling and Stunting Prevention in Toddlers: A Systematic Literature Review - Solikin, Asep; setiawan, Muhammad Andi; Putra, Andi Riswandi Buana (Universitas PGRI Yogyakarta, 2025)
Stunting in children is a serious global nutrition issue that long-term impacts health and development. This study aims to analyze the role of nutrition counseling in preventing stunting through a systematic review of 162 articles from databases such as PubMed, Google Scholar, Semantic Scholar, and Scopus, with 16 articles meeting the criteria for further analysis using NVivo and Biblioshiny. The results show that nutrition counseling can improve nutritional knowledge and child growth, although its effectiveness varies across studies. Some research, such as Nadimin et al. (2021) and Christian et al. (2020), indicates that while counseling does not directly reduce the prevalence of stunting, it does raise parental awareness about healthy feeding practices. In conclusion, a comprehensive approach is needed, including family involvement and improved access to healthcare services. Further research is recommended to broaden the scope and explore the long-term impact of these interventions. Keywords: counseling, nutrition, stunting, toddlers, systematic literature review